(untitled) (Research, Society and Development, 2021)
The gluten-free alternative flours and the application of natural fermentation in the breads production are promising technologies to improving sensory, structural and nutritional properties. The aim of this study was to evaluate the applicability and quality of gluten-free breads made with sour dough from wholegrain rice flours (BR and BRY), carioca beans (BP and BPY) and cowpea (BV and BVY). The sour doughs were prepared without and with the addition of biological yeast (Saccharomyces cerevisiae) represented by the letter “Y”. The breads made from these doughs were subjected to the analysis of: pH, titratable total acidity, color, water activity, moisture, image analysis, specific volume, instrumental texture, proximate composition and energy value. The results indicated higher ash, protein and dietary fiber content in BP and BV flours. At the end of fermentation, the BR and BRY masses showed greater acidity. The doughs made with beans showed greater expansion volumes. Lower volume, firmness and hardness were verified for BBRY bread and the opposite was verified for BVB bread. The BBV, BBVY, BBP and BBPY breads had higher ash, protein and dietary fiber contents and lower digestible carbohydrate content. BPB and BVB breads showed higher protein digestibility and the opposite was observed for BBRY (70.60%), BPBY (81.09%) and BVBY (80.89%). The use of bean flour in the preparation of breads resulted in products rich in dietary fiber and proteins, especially carioca beans.